Development of a cost-effective, recyclable and viable metal ion doped adsorbent for simultaneous adsorption and reduction of toxic Cr (VI) ions. Issue 2 (April 2021) - Singh, Veer; Singh, Jyoti; Mishra, Vishal
Abstract: Iron ions were doped on the rice husk for adsorption-cum-reduction of lethal Cr (VI) to less toxic and partially soluble Cr (III). Energy dispersive X-ray analysis and X-ray photoelectric spectroscopy disclosed the effective doping of iron on rice husk and significant reduction of Cr (VI) into Cr (III). Physico-chemical analysis exhibited that the surface of an iron doped rice husk was rough and in houses amino and hydroxyl moieties in majority together with high organic content. The maximum removal of Cr (VI) ions was observed in acidic range as the value of point zero charge was 3.32. The study of dimensionless numbers ( φ, N k and λ ) disclosed that the Cr (VI) adsorption on iron coated rice husk was principally controlled by diffusion. The suitability of acidic pH indicated that heavy protonation at FeRH surface generated the electrostatic pull of negatively charged Cr (VI) species, which led to a favorable biosorption. Only 1.32% and 0.18% deviation in experimental results was observed for undoped and iron doped rice husk, respectively in artificial neural network's correlation plot. The film and pore diffusivity coefficients along with Bangham's model study revealed that the adsorption was film diffusion limited for both types of rice husks. The maximal Cr (VI) removal was found to be 81.56% for iron doped and 43.28% for undoped rice husk. The iron doped rice husk had high regeneration capacity up to three cycles of adsorption and desorption. Cr (VI) adsorption was chemisorptive, spontaneous, endothermic, favorable and multilayer in nature. Graphical Abstract: ga1 Highlights: Development of green and viable metal ion adsorbent. Dimensionless number calculation and prediction through ANN modeling. Reduction Cr (VI) to Cr (III) on the FeRH surface. The comparative study Cr (VI) removal efficiency of RH and FeRH. The Cr (VI) concentration was reduced below the permissible limit of discharge.